Bencana Alam dan Kemiskinan di Indonesia - Heru Syah Putra (Jurnal Transformasi Administrasi, 2017)
The natural disaster has a significant effect on household’s income and expenditure. The linkage of natural disaster and income has been explored intensively. However, the linkage of natural disaster and poverty is less explored. Thus, this study aims to fill the gap by estimating the effect of natural disaster on poverty in Indonesia. This study utilizes the data from IFLS 5. Linear Probability Model (LPM) is used to estimate the probability of being poor of a household after a certain disaster. The result shows that a household that encountered a certain natural disaster has a higher probability of being poor by 4.68 percent than others. The coefficient is corrected to 2.68 after considering district fixed effect. Further, the effect of natural disaster differs regarding its type. Volcano eruption has the worst effect on poverty. A household that suffered volcano eruption has a probability of being poor by 7.84. In contrast, flood only contributes 5.85. There is no significant effect of the earthquake on poverty that may be caused by omitted variable bias as the magnitude is not controlled in this study. This study suggests three optional strategies for reducing the negative impact of the natural disaster on poverty in Indonesia. Increasing productive assets may reduce the loss and shorten the recovery period. The disaster drill is needed for increasing the preparedness of a society. Increasing the quantity and quality of disaster-resistant infrastructure is strongly advised in disaster-prone areas.